Development of a model to simulate groundwater inundation induced by sea-level rise and high tides in Honolulu, Hawaii. (1st May 2017) - Habel, Shellie; Fletcher, Charles H.; Rotzoll, Kolja; El-Kadi, Aly I.
Abstract: Many of the world's largest cities face risk of sea-level rise (SLR) induced flooding owing to their limited elevations and proximities to the coastline. Within this century, global mean sea level is expected to reach magnitudes that will exceed the ground elevation of some built infrastructure. The concurrent rise of coastal groundwater will produce additional sources of inundation resulting from narrowing and loss of the vertical unsaturated subsurface space. This has implications for the dense network of buried and low-lying infrastructure that exists across urban coastal zones. Here, we describe a modeling approach that simulates narrowing of the unsaturated space and groundwater inundation (GWI) generated by SLR-induced lifting of coastal groundwater. The methodology combines terrain modeling, groundwater monitoring, estimation of tidal influence, and numerical groundwater-flow modeling to simulate future flood scenarios considering user-specified tide stages and magnitudes of SLR. We illustrate the value of the methodology by applying it to the heavily urbanized and low-lying Waikiki area of Honolulu, Hawaii. Results indicate that SLR of nearly 1 m generates GWI across 23% of the 13 km 2 study area, threatening $5 billion of taxable real estate and 48 km of roadway. Analysis of current conditions reveals that 86% of 259 active cesspool sites in the study area are likely inundated. This suggests that cesspool effluent is currently entering coastal groundwater, which not only leads to degradation of coastal environments, but also presents a future threat to public health as GWI would introduce effluent at the ground surface. Graphical abstract: Highlights: A method for mapping sea-level rise induced groundwater inundation is presented. Method considers tidal influence and over-height of groundwater above sea level. The method is applied to the heavily urbanized Waikiki area in Honolulu, Hawaii. Future vulnerabilities to roadways, cesspools and real estate are identified. Current and future potential of widespread groundwater contamination are identified.